3D current path in stacked devices : metrics and challenges - Kor, H. B. (2011)
Although magnetic current imaging (MCI) is useful in fault isolation of devices with 2D current distributions, MCI alone cannot give the exact information of current paths in complex 3D stacked devices. Previous work has demonstrated the ability of a simulation approach to find a short circuit in 3D geometry. This approach has been challenged in the case of dense and complex 3D current paths. In this paper, the aim is to demonstrate how we can overcome this issue by using a new simulation approach instead of the previous segment by segment approach. The new approach has been validated on a complex chip with daisy chains vertically connected by vias. From the study of the simulation of three hypothesized current paths of various current lines of interest, excluding and including the interactions with neighbouring current lines (both locally and globally), it was found that interactions of a current line with its global neighbours have very important effects, compared to no interactions or only interactions with local neighbours. By simulating all the currents, it was possible to minimize the error given by the presence of several current lines in a small volume.